Profile of Self Medication Practices in the Tarramatekkeng Village Luwu District South Sulawesi - Rina Asrina; Alfreds Roosevelt; Muthmainna B; Hasma Hasma; Rusli Rusli (Media Kesehatan Politeknik Kesehatan Makassar, 2025)
Self medication is the practice of treating oneself using over the counter medicines, limited over-the-counter drugs, or prescription medications obtained from pharmacies. This practice requires adequate knowledge to ensure safe and effective use. Self medication is becoming increasingly common due to its affordability, convenience, and easy access to pharmacies and drugstores, as well as the availability of health information through various media. This study aimed to describe self-medication practices in the community of Kasumang Hamlet, Tarramatekkeng Village, especially in terms of illnesses treated, types of medications used, sources of information, places where medicines were obtained and and they purchased medicines either for immediate use or for future stock. A descriptive research design with a cross-sectional quantitative approach was employed. This study was conducted in Dusun Kasumang, Tarramatekkeng Village, Luwu Regency, from May to June 2025. The sample size was determined using the Slovin formula, resulting in a total of 81 participants. Participants were selected using purposive sampling based on predetermined inclusion criteria. Headaches were the most common reason for self-medication (20%), followed by fever (19%). The most commonly purchased drug was Paracetamol (17%), with 53% of participants buying medication at pharmacies. The main source of information was relatives (47%), and 51% of participants were currently using medication. These findings highlight the need for increased public awareness regarding the safe use of medicines, greater access to professional pharmaceutical guidance, and strengthened regulation of prescription drug sales to reduce the risk of inappropriate self-medication and protect community health